A method for preparing activated carbon for water treatment

By using beeswax and other materials to form a layered structure in the preparation of activated carbon, combined with hydrophobic modification and silk fibroin cross-linking technology, the problem of insufficient adsorption selectivity and stability of activated carbon in water treatment is solved, and its adsorption is significantly improved Capacity and mechanical properties.

CN118908207BActive Publication Date: 2025-02-11FUJIAN EXPLORATION NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411056414.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2025-02-11
Estimated Expiration
2044-08-02

AI Technical Summary

Technical Problem

In the water treatment, existing activated carbons have problems such as low adsorption selectivity, hydrophilicity, and insufficient adsorption performance of hydrophobic pollutants.

Method used

Activated carbon is prepared using beeswax and other materials, and a layered structure with a non-domained π-electron system is formed during the carbonization process. Hydrophobic modification and flexible long-chain grafting are carried out through sodium dodecyl sulfate and polyethylene glycol. A stable intersecting network is formed using the β-sheet structure of silk fibroin and glutaraldehyde cross-linking.

Benefits of technology

The adsorption capacity of activated carbon is improved, especially the adsorption capacity of hydrophobic organic pollutants, enhance its mechanical properties and durability, and improve the adsorption efficiency and stability in water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004976568150000101
    Figure BDA0004976568150000101
  • Figure BDA0004976568150000111
    Figure BDA0004976568150000111
  • Figure BDA0004976568150000112
    Figure BDA0004976568150000112
Patent Text Reader

Abstract

The present invention relates to an activated carbon for water treatment and a preparation method thereof, and belongs to the technical field of activated carbon. The preparation method comprises the treatment and activation of carbon materials, the grafting of hydrophobic groups, the grafting of long-chain flexible groups, and the cross-linking of silk protein suspension. Beeswax and other materials are used as raw materials, and sodium dodecyl sulfate and polyethylene glycol are used to perform hydrophobic modification and flexible long-chain grafting on the activated carbon. With the help of the structure of silk protein and glutaraldehyde cross-linking to form a stable intertwined network, a higher specific surface area and a more developed pore structure are obtained, the mechanical properties and durability of the activated carbon are improved, and its adsorption efficiency and stability in water treatment are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of activated carbon and relates to a method for preparing activated carbon for water treatment. Background Art

[0002] Water treatment is an important part of ensuring water quality safety and protecting the environment. Especially in the process of industrialization and urbanization, water pollution is becoming increasingly serious. These pollutants not only pose a threat to human health, but also destroy the balance of aquatic ecosystems. Activated carbon, as an efficient water treatment material, is widely used in the field of water treatment due to its high specific area, porous structure and good adsorption performance. However, there are some limitations in the use of activated carbon at this stage. First, the adsorption selectivity of traditional activated carbon is not high, and there are differences in the adsorption capacity of different pollutants; secondly, the hydrophilicity of activated carbon itself makes it easy for water molecules to occupy the adsorption site, which will also affect the adsorption performance of hydrophobic pollutants. Based on this problem, most of the modification treatments of activated carbon at this stage increase the specific surface area of ​​activated carbon or graft hydrophobic functional groups to improve the adsorption performance. However, this modification treatment has a relatively single effect and cannot guarantee the stability of the hydrophobic functional group grafting chain and the overall hydrophobic structure, so there are still limitations in application. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing activated carbon for water treatment. The present invention prepares activated carbon by using beeswax and other materials, and forms a layered structure with a non-localized π electron system during the carbonization process to enhance its adsorption capacity. At the same time, sodium dodecyl sulfate and polyethylene glycol are used to perform hydrophobic modification and flexible long chain grafting on the activated carbon to enhance its adsorption capacity and cyclic stability for hydrophobic organic pollutants. A stable intertwined network is formed through the β-folded structure of silk fibroin and glutaraldehyde cross-linking to obtain a higher specific surface area and a more developed pore structure, thereby improving the mechanical properties and durability of the activated carbon, and further improving its adsorption efficiency and stability in water treatment.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing activated carbon for water treatment, the preparation method comprising the following steps:

[0006] (1) After washing and drying material A, crushing it into 100-200 meshes, and carbonizing it under a nitrogen atmosphere to obtain a carbonized material;

[0007] (2) mixing the carbonized material and the phosphoric acid solution for 20-30 minutes, centrifuging to obtain the solid material, placing the solid material in a tube furnace for activation, washing with deionized water, and drying to obtain the activated material;

[0008] (3) mixing the activated material, sodium dodecyl sulfate, potassium persulfate and deionized water, stirring at 50-90° C. for 1-3 h, washing with deionized water, and drying to obtain product A;

[0009] (4) mixing product A, polyethylene glycol, 3-aminopropyltriethoxysilane, potassium persulfate and ethanol solution, stirring at 50-90° C. for 2-4 hours, washing with deionized water, and drying to obtain product B;

[0010] (5) After the product B and the silk fibroin suspension are uniformly mixed by ultrasonication, anhydrous ethanol is added, and a glutaraldehyde solution is added dropwise, and the mixture is stirred at 30-40°C for 4-5 hours. The mixture is centrifuged, the solid is collected, washed with deionized water, and dried to obtain activated carbon.

[0011] Furthermore, the material A in the step (1) is composed of material B and beeswax in a mass ratio of 1.47-1.82:0.24-0.41; the material B is selected from one or more of coconut shells, walnut shells, and peanut shells; and the parameters of the carbonization step are: the carbonization temperature is 500-700°C, and the carbonization time is 6-10h.

[0012] Furthermore, the mass ratio of the carbonized material and the phosphoric acid solution in step (2) is 4-6:10-14; the mass concentration of the phosphoric acid solution is 60-70wt%; the parameters of the centrifugation step are: 25°C, the centrifugal speed is 1000-3000rmp, and the centrifugation time is 10-20min; the parameters of the tubular furnace activation step are: the activation temperature is 570-610°C, and the activation time is 1.5-2.5h.

[0013] Furthermore, in the step (3), the mass ratio of the activated material, sodium dodecyl sulfate, potassium persulfate and deionized water is 1.2-1.73:0.32-0.4:0.05-0.07:4.5-5.5.

[0014] Furthermore, in the step (4), the mass ratio of the product A, polyethylene glycol, 3-aminopropyltriethoxysilane, potassium persulfate and ethanol solution is 1.35-1.63:0.2-0.32:0.38-0.6:0.08-0.12:5-6; the molecular weight of the polyethylene glycol is 4000Da; and the mass concentration of the ethanol solution is 70-80wt%.

[0015] Furthermore, the mass ratio of product B, silk fibroin suspension and anhydrous ethanol in step (5) is 1.2-1.6:2.5-3.7:8-10; the mass of the glutaraldehyde solution accounts for 1.5-3wt% of the anhydrous ethanol; the parameters of the ultrasonic treatment are: ultrasonic frequency is 30-50kHz, ultrasonic power is 250-450W, and ultrasonic temperature is 30-40°C; the parameters of the centrifugation step are: 25°C, centrifugal speed is 6000-8000rmp, and centrifugal time is 20-30min.

[0016] Furthermore, the preparation method of the silk fibroin suspension in step (5) is:

[0017] Add silk fibroin powder into deionized water, add citric acid buffer solution to adjust the pH to 4.5-5.5, stir evenly at 60-80°C and 30-50 rpm for 30-40 min, add Span-80, and add glutaraldehyde solution while stirring at 100-300 rpm. After the addition is completed, keep the temperature unchanged for 1-2 hours to obtain a silk fibroin suspension.

[0018] Furthermore, in terms of mass percentage, the mass of the silk fibroin powder accounts for 3-7wt% of the silk fibroin suspension, the mass of the Span-80 accounts for 0.8-1.6wt% of the silk fibroin suspension, and the mass of the glutaraldehyde solution accounts for 1-2wt% of the silk fibroin suspension; the concentration of the citric acid buffer solution is 100-300mmol / L.

[0019] Furthermore, the mass concentration of the glutaraldehyde solution is 0.1-0.3wt%, and the dropping speed of the glutaraldehyde solution is controlled to be 0.1-0.3mL / min.

[0020] Beneficial effects of the present invention:

[0021] (1) The present invention uses beeswax and other materials as activated carbon raw materials. During the carbonization process, the high molecular weight organic precursors of beeswax and other materials undergo pyrolysis to produce low molecular weight carbon skeletons and remove volatile components. As the heating process continues, the residual carbon atoms tend to rearrange into a layered structure with non-localized π electrons. The presence of the non-localized π electron system provides additional electron donor properties for the activated carbon, thereby enhancing the adsorption capacity of the activated carbon by means of the π-π stacking effect. In addition, beeswax has thermal stability and hydrophobicity. Its thermal stability helps to form a more uniform and stable carbon skeleton, and its hydrophobicity may help to form more micropores and mesopores, providing more opportunities for the penetration and activation of phosphoric acid solution, so that the activated carbon material has a higher specific surface area and a more developed pore structure, providing more active sites for the grafting of subsequent groups, and also enhancing the adsorption capacity of the carbon material.

[0022] (2) The sodium dodecyl hydrophobic in the present invention is composed of a hydrophilic head group and a hydrophobic tail. It combines with the oxygen-containing functional groups on the carbon surface through hydrophobic interaction to form a hydrophobic modification layer. The hydrophobic modification layer reduces the adsorption competition of water molecules, thereby improving the adsorption capacity of the carbon material for hydrophobic organic pollutants. The long chain structure of polyethylene glycol is unfolded in the pores of the carbon material. The dynamic movement in the pores can improve the fluidity in the pores and help the diffusion and transmission of molecules in the pores. The ether oxygen groups it contains can prevent the activated carbon surface from being overly hydrophobic, maintain a certain hydrophilicity, and help the dispersion and stability of the activated carbon in water. The flexibility of its molecular chain makes the activated carbon show better cyclic stability during adsorption and desorption. 3-aminopropyltriethoxysilane is hydrolyzed in water to form silanol, and its silanol group forms a covalent bond with the hydroxyl group on the carbon surface. The other end of 3-aminopropyltriethoxysilane contains an amino group, which forms a covalent bond with the terminal hydroxyl group of polyethylene glycol, so that the polyethylene glycol is grafted to the surface of the carbon material, thereby increasing the hydrophobicity and flexibility of the carbon material surface.

[0023] (3) Span-80 is added to the silk fibroin suspension of the present invention. Under heat treatment, the silk fibroin tends to form a relatively ordered and stable β-folded structure from an unstable and water-soluble spiral and non-β-folded structure. Span-80 can reduce the surface tension between water and hydrophobic substances and promote the transformation of the structure. The amino acid side chains in the structure provide abundant chemical modification sites. The hydrophobic groups and flexible long chains grafted onto the surface of the carbon material are cross-linked by glutaraldehyde. Through interaction and entanglement between molecular chains, it helps to evenly disperse in the composite material and avoid agglomeration, thereby forming a stable entangled network, improving the mechanical properties of the activated carbon such as durability and fracture resistance, and further improving the adsorption effect of the activated carbon in water treatment. DETAILED DESCRIPTION

[0024] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0025] Example 1

[0026] A method for preparing activated carbon for water treatment, the preparation method of this embodiment comprises the following steps:

[0027] (1) After washing and drying material A, crushing it into 100 meshes, and carbonizing it under a nitrogen atmosphere to obtain a carbonized material;

[0028] (2) mixing and stirring the carbonized material and the phosphoric acid solution for 20 minutes, centrifuging to obtain the solid material, placing the solid material in a tube furnace for activation, washing with deionized water, and drying to obtain the activated material;

[0029] (3) mixing the activated material, sodium dodecyl sulfate, potassium persulfate and deionized water, stirring at 50° C. for 1 h, washing with deionized water, and drying to obtain product A;

[0030] (4) mixing product A, polyethylene glycol, 3-aminopropyltriethoxysilane, potassium persulfate and ethanol solution, stirring at 50° C. for 2 h, washing with deionized water, and drying to obtain product B;

[0031] (5) After the product B and the silk fibroin suspension are uniformly mixed by ultrasonication, anhydrous ethanol is added, and a glutaraldehyde solution is added dropwise, and the mixture is stirred at 30°C for 4 hours. The mixture is centrifuged, the solid is collected, washed with deionized water, and dried to obtain activated carbon.

[0032] The material A in step (1) of this embodiment is composed of material B and beeswax in a mass ratio of 1.47:0.24; the material B of this embodiment is coconut shell; the parameters of the carbonization step of this embodiment are: the carbonization temperature is 500° C., and the carbonization time is 6 hours.

[0033] The mass ratio of the carbonized material and the phosphoric acid solution in step (2) of this embodiment is 4:10; the mass concentration of the phosphoric acid solution of this embodiment is 60wt%; the parameters of the centrifugation step of this embodiment are: 25°C, the centrifugal speed is 1000rmp, and the centrifugation time is 10min; the parameters of the tubular furnace activation step of this embodiment are: the activation temperature is 570°C, and the activation time is 1.5h.

[0034] The mass ratio of the activated material, sodium dodecyl sulfate, potassium persulfate and deionized water in step (3) of this embodiment is 1.2:0.32:0.05:4.5.

[0035] The mass ratio of product A, polyethylene glycol, 3-aminopropyltriethoxysilane, potassium persulfate and ethanol solution in step (4) of this embodiment is 1.35:0.2:0.38:0.08:5; the molecular weight of polyethylene glycol in this embodiment is 4000Da; the mass concentration of the ethanol solution in this embodiment is 70wt%.

[0036] The mass ratio of product B, silk fibroin suspension and anhydrous ethanol in step (5) of this embodiment is 1.2:2.5:8; the mass of glutaraldehyde solution in this embodiment accounts for 1.5wt% of anhydrous ethanol; the parameters of ultrasonic treatment in this embodiment are: ultrasonic frequency of 30kHz, ultrasonic power of 250W, and ultrasonic temperature of 30°C; the parameters of the centrifugation step in this embodiment are: 25°C, centrifugal speed of 6000rmp, and centrifugal time of 20min.

[0037] The preparation method of the silk fibroin suspension in step (5) of this embodiment is:

[0038] Add silk fibroin powder into deionized water, add citric acid buffer solution to adjust the pH to 4.5, stir evenly at 60°C and 30 rpm for 30 min, add Span-80, and add glutaraldehyde solution while stirring at 100 rpm. After the addition is completed, keep the temperature unchanged for 1 hour to obtain a silk fibroin suspension.

[0039] Calculated by mass percentage, the mass of the silk fibroin powder in this embodiment accounts for 3wt% of the silk fibroin suspension, the mass of Span-80 in this embodiment accounts for 0.8wt% of the silk fibroin suspension, and the mass of the glutaraldehyde solution in this embodiment accounts for 1wt% of the silk fibroin suspension; the concentration of the citric acid buffer solution in this embodiment is 100mmol / L.

[0040] The mass concentration of the glutaraldehyde solution in this embodiment is 0.1 wt %, and the dropping speed of the glutaraldehyde solution in this embodiment is controlled to be 0.1 mL / min.

[0041] Example 2

[0042] A method for preparing activated carbon for water treatment, the preparation method of this embodiment comprises the following steps:

[0043] (1) After washing and drying material A, crushing it to 200 mesh, and carbonizing it under a nitrogen atmosphere to obtain a carbonized material;

[0044] (2) mixing and stirring the carbonized material and the phosphoric acid solution for 30 minutes, centrifuging to obtain the solid material, placing the solid material in a tube furnace for activation, washing with deionized water, and drying to obtain the activated material;

[0045] (3) mixing the activated material, sodium dodecyl sulfate, potassium persulfate and deionized water, stirring at 90° C. for 1-3 h, washing with deionized water, and drying to obtain product A;

[0046] (4) mixing product A, polyethylene glycol, 3-aminopropyltriethoxysilane, potassium persulfate and ethanol solution, stirring at 90° C. for 4 h, washing with deionized water, and drying to obtain product B;

[0047] (5) After the product B and the silk fibroin suspension are uniformly mixed by ultrasonication, anhydrous ethanol is added, and a glutaraldehyde solution is added dropwise, and the mixture is stirred at 40°C for 5 hours. The mixture is centrifuged, the solid is collected, washed with deionized water, and dried to obtain activated carbon.

[0048] The material A in step (1) of this embodiment is composed of material B and beeswax in a mass ratio of 1.82:0.41; the material B of this embodiment is coconut shell; the parameters of the carbonization step of this embodiment are: the carbonization temperature is 700° C., and the carbonization time is 10 h.

[0049] The mass ratio of the carbonized material and the phosphoric acid solution in step (2) of this embodiment is 6:14; the mass concentration of the phosphoric acid solution of this embodiment is 70wt%; the parameters of the centrifugation step of this embodiment are: 25°C, the centrifugal speed is 3000rmp, and the centrifugation time is 20min; the parameters of the tubular furnace activation step of this embodiment are: the activation temperature is 610°C, and the activation time is 2.5h.

[0050] The mass ratio of the activated material, sodium dodecyl sulfate, potassium persulfate and deionized water in step (3) of this embodiment is 1.73:0.4:0.07:5.5.

[0051] The mass ratio of product A, polyethylene glycol, 3-aminopropyltriethoxysilane, potassium persulfate and ethanol solution in step (4) of this embodiment is 1.63:0.32:0.6:0.12:6; the molecular weight of polyethylene glycol in this embodiment is 4000Da; the mass concentration of the ethanol solution in this embodiment is 80wt%.

[0052] The mass ratio of product B, silk fibroin suspension and anhydrous ethanol in step (5) of this embodiment is 1.6:3.7:10; the mass of glutaraldehyde solution in this embodiment is 3wt% of anhydrous ethanol; the parameters of ultrasonic treatment in this embodiment are: ultrasonic frequency is 50kHz, ultrasonic power is 450W, and ultrasonic temperature is 40°C; the parameters of the centrifugation step in this embodiment are: 25°C, centrifugal speed is 8000rmp, and centrifugal time is 30min.

[0053] The preparation method of the silk fibroin suspension in step (5) of this embodiment is:

[0054] Add silk fibroin powder into deionized water, add citric acid buffer solution to adjust the pH to 5.5, stir evenly at 80°C and 50 rpm for 40 min, add Span-80, and add glutaraldehyde solution while stirring at 300 rpm. After the addition is completed, keep the temperature unchanged for 2 h to obtain a silk fibroin suspension.

[0055] In terms of mass percentage, the mass of the silk fibroin powder in this embodiment accounts for 7wt% of the silk fibroin suspension, the mass of Span-80 in this embodiment accounts for 1.6wt% of the silk fibroin suspension, and the mass of the glutaraldehyde solution in this embodiment accounts for 2wt% of the silk fibroin suspension; the concentration of the citric acid buffer solution in this embodiment is 300mmol / L.

[0056] The mass concentration of the glutaraldehyde solution in this embodiment is 0.3 wt %, and the dropping speed of the glutaraldehyde solution in this embodiment is controlled to be 0.3 mL / min.

[0057] Example 3

[0058] A method for preparing activated carbon for water treatment, the preparation method of this embodiment comprises the following steps:

[0059] (1) After washing and drying material A, the material A is crushed to 150 meshes, and then carbonized under a nitrogen atmosphere to obtain a carbonized material;

[0060] (2) mixing the carbonized material and the phosphoric acid solution for 25 minutes, centrifuging to obtain the solid material, placing the solid material in a tube furnace for activation, washing with deionized water, and drying to obtain the activated material;

[0061] (3) mixing the activated material, sodium dodecyl sulfate, potassium persulfate and deionized water, stirring at 70° C. for 2 h, washing with deionized water, and drying to obtain product A;

[0062] (4) mixing product A, polyethylene glycol, 3-aminopropyltriethoxysilane, potassium persulfate and ethanol solution, stirring at 70° C. for 3 h, washing with deionized water, and drying to obtain product B;

[0063] (5) After the product B and the silk fibroin suspension are uniformly mixed by ultrasonication, anhydrous ethanol is added, and a glutaraldehyde solution is added dropwise, and the mixture is stirred at 35°C for 4.5 hours. The mixture is centrifuged, the solid is collected, washed with deionized water, and dried to obtain activated carbon.

[0064] The material A in step (1) of this embodiment is composed of material B and beeswax in a mass ratio of 1.64:0.32; the material B of this embodiment is coconut shell; the parameters of the carbonization step of this embodiment are: the carbonization temperature is 600° C., and the carbonization time is 8 hours.

[0065] The mass ratio of the carbonized material and the phosphoric acid solution in step (2) of this embodiment is 5:12; the mass concentration of the phosphoric acid solution of this embodiment is 65wt%; the parameters of the centrifugation step of this embodiment are: 25°C, the centrifugal speed is 2000rmp, and the centrifugation time is 15min; the parameters of the tubular furnace activation step of this embodiment are: the activation temperature is 590°C, and the activation time is 2h.

[0066] The mass ratio of the activated material, sodium dodecyl sulfate, potassium persulfate and deionized water in step (3) of this embodiment is 1.46:0.36:0.06:5.

[0067] The mass ratio of product A, polyethylene glycol, 3-aminopropyltriethoxysilane, potassium persulfate and ethanol solution in step (4) of this embodiment is 1.99:0.26:0.49:0.1:5.5; the molecular weight of polyethylene glycol in this embodiment is 4000Da; the mass concentration of the ethanol solution in this embodiment is 75wt%.

[0068] The mass ratio of product B, silk fibroin suspension and anhydrous ethanol in step (5) of this embodiment is 1.4:3.1:9; the mass of the glutaraldehyde solution of this embodiment accounts for 2.25wt% of anhydrous ethanol; the parameters of the ultrasonic treatment of this embodiment are: ultrasonic frequency of 40kHz, ultrasonic power of 350W, and ultrasonic temperature of 35°C; the parameters of the centrifugation step of this embodiment are: 25°C, centrifugal speed of 7000rmp, and centrifugal time of 25min.

[0069] The preparation method of the silk fibroin suspension in step (5) of this embodiment is:

[0070] Add silk fibroin powder into deionized water, add citric acid buffer solution to adjust the pH to 5, stir evenly at 70°C and 40 rpm for 35 min, add Span-80, and add glutaraldehyde solution while stirring at 200 rpm. After the addition is completed, keep the temperature unchanged for 1.5 h to obtain a silk fibroin suspension.

[0071] Calculated by mass percentage, the mass of the silk fibroin powder of this embodiment accounts for 5wt% of the silk fibroin suspension, the mass of Span-80 of this embodiment accounts for 1.2wt% of the silk fibroin suspension, and the mass of the glutaraldehyde solution of this embodiment accounts for 1.5wt% of the silk fibroin suspension; the concentration of the citric acid buffer solution of this embodiment is 200mmol / L.

[0072] The mass concentration of the glutaraldehyde solution in this embodiment is 0.2 wt %, and the dropping speed of the glutaraldehyde solution in this embodiment is controlled to be 0.2 mL / min.

[0073] Comparative Example 1

[0074] On the basis of Example 3, the beeswax was removed and replaced with an equal weight of coconut shell, and other conditions were consistent with Example 3.

[0075] Comparative Example 2

[0076] Based on Example 3, step (3) was removed and other conditions were the same as those in Example 3.

[0077] Comparative Example 3

[0078] Based on Example 3, step (4) was removed and other conditions were the same as those in Example 3.

[0079] Comparative Example 4

[0080] On the basis of Example 3, the polyethylene glycol in step (4) was removed and replaced with an equal weight of 3-aminopropyltriethoxysilane, and the other conditions were consistent with Example 3.

[0081] Comparative Example 5

[0082] On the basis of Example 3, Span-80 in step (5) was removed and replaced with an equal weight of deionized water. Other conditions were the same as in Example 3.

[0083] 1. Specific surface area and pore volume determination

[0084] The activated carbon obtained in Examples 1-3 and Comparative Examples 1-5 was used as a sample, and the specific surface area and pore volume of the sample were tested according to the method specified in "DL / T 582-1995 Guidelines for Performance Test of Activated Carbon for Water Treatment". The test results are shown in Table 1 below.

[0085] Table 1 Specific surface area and pore volume measurement results

[0086]

[0087]

[0088] It can be seen from Table 1 above that the activated carbons prepared in Examples 1-3 of the present invention have a higher specific surface area and a more developed pore structure. Beeswax is used in conjunction with other materials as the activated carbon raw materials. As the heating process continues, the removal of low molecular weight carbon skeletons and volatile components helps to form more micropores and mesopores, providing abundant active sites for subsequent activation and grafting, so that the hydrophobic groups, flexible long chains and silk fibroin suspensions are uniformly and stably cross-linked to form a network structure, thereby obtaining a relatively excellent specific surface area and pore structure.

[0089] 2. Activated carbon performance test

[0090] The activated carbon obtained in Examples 1-3 and Comparative Examples 1-5 was used as samples, and the performance of the samples was tested.

[0091] The adsorption value of activated carbon for methylene blue was tested according to GB / T 12496.10-1999 "Test method for wood activated carbon - Determination of adsorption value of methylene blue"; the adsorption value of activated carbon for quinine sulfate was tested according to GN / T 12496.11-1999 "Test method for wood activated carbon - Determination of adsorption value of quinine sulfate"; the content of heavy metals was tested according to GB / T 12496.22-1999 "Test method for wood activated carbon - Determination of heavy metals"; the content of sulfide was tested according to GB / T 12496.15-1999 "Test method for wood activated carbon - Determination of sulfide". The test results are shown in Table 2 below.

[0092] Table 2 Activated carbon performance test results

[0093]

[0094]

[0095] It can be seen from Table 2 above that the changes in the preparation methods of activated carbon in Examples 1-3, in addition, the absence of beeswax, hydrophobic groups or flexible long chains directly or indirectly affects the specific surface area and pore formation of activated carbon, thereby affecting the adsorption capacity of activated carbon; in Example 4, 3-aminopropyltriethoxysilane is used to replace polyethylene glycol, which cannot achieve the diffusion and transmission of the long chain structure to the adsorbed components of the present invention, and the hydrophobicity of beeswax and the subsequent introduction of hydrophobic groups may cause excessive hydrophobicity on the surface of activated carbon, affecting the adsorption capacity of activated carbon; in Example 5, Span-80 is removed, which may reduce the transformation of the β-folded structure in silk fibroin and the uniform dispersion of the silk fibroin suspension on the surface of the carbon material, thereby affecting the subsequent formation of a stable entangled network and affecting the adsorption performance of activated carbon.

[0096] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing activated carbon for water treatment, characterized in that: The preparation method comprises the following steps: (1) After washing and drying material A, crushing it to 100-200 mesh, and carbonizing it under a nitrogen atmosphere to obtain a carbonized material; (2) After the carbonized material and the phosphoric acid solution are mixed and stirred for 20-30 minutes, the solid material is centrifuged and placed in a tube furnace for activation, washed with deionized water, and dried to obtain the activated material; (3) Mixing the activated material, sodium dodecyl sulfate, potassium persulfate and deionized water, stirring at 50-90° C. for 1-3 h, washing with deionized water, and drying to obtain product A; (4) mixing product A, polyethylene glycol, 3-aminopropyltriethoxysilane, potassium persulfate and ethanol solution, stirring at 50-90° C. for 2-4 hours, washing with deionized water, and drying to obtain product B; (5) After the product B and the silk fibroin suspension are uniformly mixed by ultrasonication, anhydrous ethanol is added, and the glutaraldehyde solution is added dropwise, and the mixture is stirred at 30-40°C for 4-5 hours, centrifuged, and the solid is taken out, washed with deionized water, and dried to obtain activated carbon; The material A in step (1) is composed of material B and beeswax in a mass ratio of 1.47-1.82:0.24-0.41; the material B is selected from one or more of coconut shells, walnut shells, and peanut shells; the parameters of the carbonization step are: carbonization temperature is 500-700°C, and carbonization time is 6-10h; The preparation method of the silk fibroin suspension in step (5) is as follows: Add silk fibroin powder into deionized water, add citric acid buffer solution to adjust the pH to 4.5-5.5, stir evenly at 60-80°C and 30-50 rpm for 30-40 min, add Span-80, and add glutaraldehyde solution while stirring at 100-300 rpm. After the addition is completed, keep the temperature unchanged for 1-2 hours to obtain a silk fibroin suspension.

2. The method for preparing activated carbon for water treatment according to claim 1, characterized in that: The mass ratio of the carbonized material to the phosphoric acid solution in step (2) is 4-6:10-14; the mass concentration of the phosphoric acid solution is 60-70wt%; the parameters of the centrifugation step are: 25°C, the centrifugal speed is 1000-3000rmp, and the centrifugal time is 10-20min; the parameters of the tubular furnace activation step are: the activation temperature is 570-610°C, and the activation time is 1.5-2.5h.

3. The method for preparing activated carbon for water treatment according to claim 1, characterized in that: The mass ratio of the activated material, sodium dodecyl sulfate, potassium persulfate and deionized water in step (3) is 1.2-1.73:0.32-0.4:0.05-0.07:4.5-5.

5.

4. The method for preparing activated carbon for water treatment according to claim 1, characterized in that: The mass ratio of the product A, polyethylene glycol, 3-aminopropyltriethoxysilane, potassium persulfate and ethanol solution in step (4) is 1.35-1.63:0.2-0.32:0.38-0.6:0.08-0.12:5-6; the molecular weight of the polyethylene glycol is 4000Da; and the mass concentration of the ethanol solution is 70-80wt%.

5. The method for preparing activated carbon for water treatment according to claim 1, characterized in that: The mass ratio of the product B, the silk fibroin suspension and the anhydrous ethanol in the step (5) is 1.2-1.6:2.5-3.7:8-10; the mass of the glutaraldehyde solution accounts for 1.5-3wt% of the anhydrous ethanol; the parameters of the ultrasonic treatment are: ultrasonic frequency of 30-50kHz, ultrasonic power of 250-450W, and ultrasonic temperature of 30-40°C; the parameters of the centrifugation step are: 25°C, centrifugal speed of 6000-8000rmp, and centrifugal time of 20-30min.

6. A method for preparing activated carbon for water treatment according to any one of claims 1 to 5, characterized in that: The mass concentration of the glutaraldehyde solution is 0.1-0.3wt%, and the dropping speed of the glutaraldehyde solution is controlled to be 0.1-0.3mL / min.

Citation Information

Patent Citations

  • Preparation method of silk fibroin bioactive material

    CN108330547A

  • Preparation method of activated carbon material surface hydrophobic protective layer

    CN111589414A